UTILIZATION OF BLACK SOLDIER FLY MAGGOT (Hermetia illucens) AND CASSAVA PULP (Manihot esculenta) AS ALTERNATIVE FEED FOR THE GROWTH OF AFRICAN CATFISH (Clarias gariepinus) - Mahmud Rudini; Uun Febriyani; Rizki Saputra; Eka Candra Kurniawati (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2026)
The high cost of commercial pellet feed represents a major constraint in African catfish (Clarias gariepinus) aquaculture, necessitating the development of alternative feeds derived from locally available organic waste sources. This study evaluated a combined feed formulation based on Black Soldier Fly larvae (Hermetia illucens) and cassava pulp (Manihot esculenta) at different proportions to assess its effects on the growth performance of African catfish. The experiment was conducted in Trimo Harjo Village, South Sumatra, from December 2024 to January 2025, using a Completely Randomized Design with four treatments and three replications. A total of 360 fish were used as the experimental units. Growth performance was evaluated based on absolute weight gain, weight gain percentage, absolute length, and feed conversion ratio (FCR), and water quality parameters were monitored as supporting variables. Data were analyzed using analysis of variance (ANOVA). The results showed that treatment P1 (75% maggot flour and 25% cassava pulp) produced the best growth performance, with an absolute weight gain of 8.66 g, weight gain of 28.88%, and FCR of 1.66, which was comparable to that of the control feed. The water quality parameters remained within acceptable ranges throughout the study. In conclusion, feed formulations based on organic waste, particularly the combination of maggot flour and cassava pulp, have strong potential as efficient and sustainable alternatives to commercial feed in the aquaculture of African catfish.